2014
DOI: 10.1177/1206331213508483
|View full text |Cite
|
Sign up to set email alerts
|

Getting Ready to Move as a Couple

Abstract: The article focuses on how students in a Lindy Hop dance class move into a complex mobile formation as a sequentially relevant response to a directive embedded in the teachers’ verbal and embodied instructions of the next task for practice. This sequence of actions accomplishes a transition from a stationary constellation of observing students to a mobile circle of practicing dance couples. The article describes in detail how instruction is turned into practice in an emergent way, in and through the simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 19 publications
(17 reference statements)
0
23
0
4
Order By: Relevance
“…As an example, we may consider couples doing grocery shopping together at the supermarket (see e.g., De Stefani, 2013), students in a peer group choosing their next learning activities (Kämäräinen et al, 2020), and family members together interpreting inkplot images in a psychological test (Siitonen and Wahlberg, 2015). However, empirical research on naturally occurring joint decisionmaking interaction has shown it to be a complex interactional endeavor (Bilmes, 1981;Tysoe, 1984;Boden, 1994;Huisman, 2001;Clifton, 2009;Asmuss and Oshima, 2012;Siitonen and Wahlberg, 2015). It involves the use of multiple resources: syntax, lexical choices, prosody, body postures, material objects, and gaze, in and through which the participants manage their level of participation and the relative distribution of agency during the different phases of the process in contextually appropriate ways (Stivers, 2005;Stevanovic, 2012b;De Stefani, 2013;Stevanovic, 2013a;Kushida and Yamakawa, 2015;Stevanovic, 2015;Stevanovic et al, 2017).…”
Section: Joint Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, we may consider couples doing grocery shopping together at the supermarket (see e.g., De Stefani, 2013), students in a peer group choosing their next learning activities (Kämäräinen et al, 2020), and family members together interpreting inkplot images in a psychological test (Siitonen and Wahlberg, 2015). However, empirical research on naturally occurring joint decisionmaking interaction has shown it to be a complex interactional endeavor (Bilmes, 1981;Tysoe, 1984;Boden, 1994;Huisman, 2001;Clifton, 2009;Asmuss and Oshima, 2012;Siitonen and Wahlberg, 2015). It involves the use of multiple resources: syntax, lexical choices, prosody, body postures, material objects, and gaze, in and through which the participants manage their level of participation and the relative distribution of agency during the different phases of the process in contextually appropriate ways (Stivers, 2005;Stevanovic, 2012b;De Stefani, 2013;Stevanovic, 2013a;Kushida and Yamakawa, 2015;Stevanovic, 2015;Stevanovic et al, 2017).…”
Section: Joint Decision-makingmentioning
confidence: 99%
“…In contrast, the bodily dimension of the participants' interactional conduct is more flexible in allowing two or more participants to construct the action underway as joint (see Stevanovic and Peräkylä, 2015). Such collaborative aspects of action are highlighted, for example, when participants in interaction smile and laugh together (Kangasharju and Nikko, 2009), move as a dancing couple (Broth and Keevallik, 2014), and synchronize their body sways during conversational transitions (Stevanovic et al, 2017). In this paper, the degree of fission vs. fusion in the participants' moment-by-moment unfolding relation toward each other and toward the action or activity underway will be considered in the context of responses to proposals during joint decision-making interaction.…”
Section: Introduction Multimodal Action Packages and Agencymentioning
confidence: 99%
“…This turn toward mobility has been through undertaking studies of the vehicular, or, to put it another way, how people do things with, and through, moving as a vehicle. The vehicular units in question might be pedestrians entering a building (Weilenmann, Normark, & Laurier, 2014), a couple travelling by car (Mondada, 2012), a small aircraft landing (Nevile, 2004) or a couple doing Lindy Hop (Broth & Keevallik, 2014). Across these varied settings the studies have been concerned with, firstly, how people jointly coordinate and accomplish their mobility on a moment-by-moment basis and, secondly, how they do this as particular categories of social unit.…”
Section: Doing Things With Walkingmentioning
confidence: 99%
“…The 'embodied turn' in CA studies (Nevile, 2015) has emphasised how participants use conventionalised sequences of embodied talk, gesture, and body orientation to pursue -or to constrain and reorganise courses of situated social action (C. Goodwin, 1981;Haddington et al, 2013;Hazel, Mortensen, & Rasmussen, 2014;Heath, 1984;Schegloff, 1985). CA studies of Lindy hop workshops (Broth & Keevallik, 2014;Keevallik, 2014) show how dance instructors combine talk, partnered movement and 'bodily-vocal demonstrations' as instructions for students to follow -and as 'corrections' for when students visibly deviate from a normatively adequate response (Keevallik, 2010). In these situations, teachers and students, or storytellers and recipients encounter 'polythetic' moments where their responses can uphold, abort, or modify the overall course of action.…”
Section: Studying the Attention Structure Of An Audience Through Rhythmmentioning
confidence: 99%
“…In the setting of the Lindy hop Jack and Jill, these responses provide detailed and ongoing evidence through participants' displays of rhythmical involvement. CA studies of the 'choral production' (Lerner, 2002) of action and gesture by multiple speakers simultaneously, and how bodily-vocal actions are produced in dance instruction (Keevallik, 2010(Keevallik, , 2014) also highlight how different kinds of projectability and rhythmical timing (Broth & Keevallik, 2014) This claim suggests the possibility of extending studies of dance performance settings using collections of cases to refine and generalise characterisations of how rhythmical embodied actions are formed and recognised by participants. However, Hazel et al (2014) describes this as a "CA paradigm" and points to some possible problems with this approach even where participants' talk is also available, citing ongoing debate as to whether (and how) complex embodied displays can be collected and studied in this way.…”
Section: Embodied Action Built With Non-vocal Resourcesmentioning
confidence: 99%